The Unexamined Staff Report: Results From an Evaluation of a National Sample. Issue 1 (2nd January 2016) - Johnson, Bonnie J.; Lyles, Ward
Abstract : Problem, research strategy, and findings: Municipal planners write staff reports reviewing development applications to submit to planning and zoning commissions. Staff reports are probably planners' most common, but least studied, work products. A small literature provides -guidance on writing better staff reports, but questions remain: What makes a quality staff report; what are their contents; and what is the state of today's staff reports? We summarize the literature on writing staff reports and develop a tool to assess the content of a national sample of staff reports. We analyze whether staff reports include traditional and modern elements. We find that many staff reports provide traditional basic information, but do not summarize that information or use modern formatting tools to make text more comprehensible. Most staff reports reference the comprehensive plan but rarely cite the future land use map or plans of adjacent jurisdictions. Many mention checking traditional public facilities like roads, but rarely list parks or pedestrian or cycling facilities. Most do not include maps, arguments for recommendations, or references to soliciting public input. Takeaway for practice: Planning departments can improve staff reports through simple changes in report organization and graphics. Planners can use this assessment tool to evaluate the strengths and weaknesses of their staff reports, and scholars can use this approach to analyze how staff reports affect the quality of decision making.